The Determinants of the Life Cycle Stages of Brazilian Public Companies: A Study Based on Financial-Accounting Variables - Wando Belffi da Costa; Marcelo Alvaro da Silva Macedo; Karen Yukari Yokoyama; José Elias Feres de Almeida (BBR: Brazilian Business Review)
This paper analyses the relation between firms’ life cycles stages according to Dickinson’s (2011) definition and accounting and financial ratios. We applied multinomial logistic regression analysis on a sample of 1,515 observations of public companies listed on BM&FBOVESPA between 2005 and 2012. Based on the literature about firms’ life cycle stages (YAN; ZHAO, 2010; MILLER; FRIESEN, 1984; FAMA; FRENCH, 2001) the accounting and financial ratios used were dividends distribution, leverage, market-to-book, return on equity, firm size and revenue growth. The results show that leverage, dividends distribution, market-to-book, return on equity, firm size and revenue growth could be used as explanatory factors to classify firms’ life cycle stages.